Psychology of Religion - Barrett, J (Routledge, 2010)
Psychology of religion is essentially as old as psychology itself, with over a hundred years of history and claiming some of psychology’s most notable characters as contributors, including William James, Sigmund Freud, Gordon Allport, and Jean Piaget. In recent years, this subfield of psychology has risen in prominence. Sectarian violence, secularization, the ‘culture wars’, and increase in cross-cultural and cross-religious contact through migration, urbanization, and globalization have all contributed to heightened interest in questions such as: where do religious beliefs come from? Why do they seem to motivate behaviour so powerfully? Is religious belief and practice good or bad for us? Does religious belief assist or hinder morality?